Bioterrorism program - Gordon, Bruce; UniversityOfHealthCare (Los Angeles, CA : UniversityofHealthCare, 2004)
Combined seven bioterrorism courses covering some of the deadliest risks: anthrax, botulism, hemorrhagic fever viruses, plague, radiation, smallpox, and tularemia.
Title from disc label.
"For healthcare workers and public officers (allied health, nurses, doctors, public health workers, EMS workers, other emergency, safety fire, police, and disaster planning and response personnel) and the public, detailed introduction on infection and treatment"--Manual cover.
System requirements for Windows: Pentium-based IBM PC or compatible; Windows 95/98/ME/2000/XP; Internet Explorer 4.0 or compatible Web browser; CD-ROM drive.
Keywords: Bioterrorism